PKM Sport Massage bagi Masyarakat Desa Karimunjawa Kabupaten Jepara - Hudah, Maftuhin; Nizaruddin, Nizaruddin; Murtianto, Yanuar Hery; Drifanda, Valdyan (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of this community service is: 1) to provide knowledge to the people of Karimunjawa Village, Jepara Regency in understanding basic sports massage, 2) to provide skills for handling sports massage and sports injuries. The sport massage activity for the people of Karimunjawa village, Jepara Regency, which will take part in 20 residents and youth youth organizations, will be held in April. The methods used are demonstrations, questions and answers, problem solving, and direct practice of the massage process. The results of the activity are as follows: 1) Karimunjawa village residents can know the stages of handling sports massage and sports injuries, 2) Karimunjawa village residents feel satisfied with the results of the training and hope that training will be held at a broader stage regarding knowledge of injury management using the community's sports massage approach Karimun Java village, Karimun Java sub-district, Jepara regency. As suggestions during the training activities, including: 1) injury management activities using a sports massage approach can be carried out for the entire community of Karimunjawa village, Jepara district, (2) it is an opportunity for residents of Karimunjawa village, Karimunjawa subdistrict, Jepara district.